(untitled) (Journal of Telenursing (JOTING), 2023)
This study aimed to provide generalist nurse intervention to adolescent clients with situational low self-esteem. The method used was a case study approach with one respondent, carried out for two days on 1-2 April 2021. The results obtained were that generalist therapy was proven to increase adolescent self-esteem. Generalist therapy has proven effective with specialist nursing therapy, including supportive therapy and family psychoeducation. Keywords: Situational low self-esteem, Adolescents, Glandular TB, Generalist Nurse Therapy